FEM-Based Methodology for the Design of Reduced Scale Representative Experimental Testing Allowing the Characterization of Defect Evolution during Hot Rolling of Bars - Corentin Pondaven; Laurent Langlois; Régis Bigot; Damien Chevalier (Metals, 2020)
Defects generated during the casting process of steel can be reduced by forming processes such as hot rolling. During these processes the effective strain, the temperature, the stress state and the alternation of the forming direction all influence the defect evolution. Analytical or numerical models are available in the literature to predict the defect evolution. However, experiments have to be carried out to identify the parameters of these models. Thus, the quality of the identification depends on the representativeness of the experiments with respect to the industrial forming process. This paper proposes a methodology to design reduced scale experiments with an improved level of representativeness. This methodology consists first in the identification of the thermomechanical parameters driving the defect evolution and the quantification of these parameters in the industrial process by FEM simulation. These last results are then utilised as criteria for the representative experiment design. In this work the methodology is applied to the rolling of bars. The representative experiment consists of successive forming operations of a cylindrical sample between shaped anvils reproducing the roll shape at a 1:10 scale. A validation is finally achieved by reproducing qualitative results concerning the evolution of voids in the vicinity of hard inclusions.